Pharmacokinetics and safety of PC-SOD, a lecithinized recombinant superoxide dismutase, in healthy Chinese subjects: A phase 1, randomized, placebo-controlled, dose-escalation study - Chen, Rui; Zhao, Qian; Wu, Ni; Zhong, Wen; Jin, Xin; Liu, Chunyan; Zhu, Zhenyu; Hu, Pei (International journal of clinical pharmacology and therapeutics, 2019)
To evaluate the pharmacokinetics of PC-SOD after single intravenous administration and its safety profile in healthy Chinese subjects.OBJECTIVESTo evaluate the pharmacokinetics of PC-SOD after single intravenous administration and its safety profile in healthy Chinese subjects.This was a phase 1, randomized, double-blind, placebo-controlled, sequential, single-dose, and dose-escalation study. The study was done in 4 cohorts and a total of 40 subjects received a single dose of PC-SOD (from 20 to 160 mg). There were 12 subjects in each dose group (10 active treatments and 2 placebos), except a 20-mg group, in which all 4 subjects were given active treatment. Serial venous blood samples were collected up to 168 hours after dosing. Serum samples were analyzed using an enzyme-linked immunosorbent assay. Pharmacokinetic parameters of PC-SOD were calculated via noncompartmental analysis using the WinNonlin.MATERIALS AND METHODSThis was a phase 1, randomized, double-blind, placebo-controlled, sequential, single-dose, and dose-escalation study. The study was done in 4 cohorts and a total of 40 subjects received a single dose of PC-SOD (from 20 to 160 mg). There were 12 subjects in each dose group (10 active treatments and 2 placebos), except a 20-mg group, in which all 4 subjects were given active treatment. Serial venous blood samples were collected up to 168 hours after dosing. Serum samples were analyzed using an enzyme-linked immunosorbent assay. Pharmacokinetic parameters of PC-SOD were calculated via noncompartmental analysis using the WinNonlin.After intravenous administration, PC-SOD reached the peak concentration quickly with a median tmax of 0.5 - 1.3 hours across all dose cohorts. After reaching Cmax, the mean T1/2 was 35.9 - 42.3 hours, which was independent of dose. The CL and Vz were 0.13 L/h and 6.72 L, 0.13 L/h and 7.33 L, and 0.11 L/h and 6.88 L for the 40, 80, and 160 mg dose cohorts, respectively. Over the dose range of 20 - 160 mg, the mean Cmax increased from 5,546.6 to 44,145.2 h×ng/mL and AUClast increased from 117,464.5 to 1,348,209.4 h×ng/mL. The 90% CI for β of AUC or Cmax slightly exceeded the criterion, indicating that there was approximate dose proportionality over the range of 20 - 160 mg or 40 - 160 mg of PC-SOD. Generally, PC-SOD was well tolerated in doses up to 160 mg in healthy Chinese subjects. Reversible elevated blood triglyceride levels were reported in 2 subjects as moderate adverse events, and all other reported adverse events were considered to be mild. The possibility of a drug hypersensitivity syndrome was not high for PC-SOD in Chinese subjects based on current data.RESULTSAfter intravenous administration, PC-SOD reached the peak concentration quickly with a median tmax of 0.5 - 1.3 hours across all dose cohorts. After reaching Cmax, the mean T1/2 was 35.9 - 42.3 hours, which was independent of dose. The CL and Vz were 0.13 L/h and 6.72 L, 0.13 L/h and 7.33 L, and 0.11 L/h and 6.88 L for the 40, 80, and 160 mg dose cohorts, respectively. Over the dose range of 20 - 160 mg, the mean Cmax increased from 5,546.6 to 44,145.2 h×ng/mL and AUClast increased from 117,464.5 to 1,348,209.4 h×ng/mL. The 90% CI for β of AUC or Cmax slightly exceeded the criterion, indicating that there was approximate dose proportionality over the range of 20 - 160 mg or 40 - 160 mg of PC-SOD. Generally, PC-SOD was well tolerated in doses up to 160 mg in healthy Chinese subjects. Reversible elevated blood triglyceride levels were reported in 2 subjects as moderate adverse events, and all other reported adverse events were considered to be mild. The possibility of a drug hypersensitivity syndrome was not high for PC-SOD in Chinese subjects based on current data.Single intravenous administrations of PC-SOD in doses up to 160 mg were well tolerated in healthy Chinese subjects. The prolonged half-life of PC-SOD was confirmed and independent of dose. Over the range of 20 - 160 mg, PC-SOD showed approximate dose proportionality. These findings suggest that it is worthwhile to investigate PC-SOD in clinical conditions characterized by a high radical overload.CONCLUSIONSingle intravenous administrations of PC-SOD in doses up to 160 mg were well tolerated in healthy Chinese subjects. The prolonged half-life of PC-SOD was confirmed and independent of dose. Over the range of 20 - 160 mg, PC-SOD showed approximate dose proportionality. These findings suggest that it is worthwhile to investigate PC-SOD in clinical conditions characterized by a high radical overload.